Educação profissional e formação humana: as (im)possibilidades de formação omnilateral no modo de produção capitalista - Pires, Adriane de Oliveira (2021)
This research investigated the (im)possibilities of omnilateral training in the capitalist mode of production, within the scope of professional education in Brazil. Having professional education as a guiding axis, the research questions the possibilities and impossibilities of an omnilateral human formation in the context of professional education in a society with a capitalist mode of production, such as in Brazil. Seeking to consolidate an understanding of omnilateral training, education and work, in the Marxian sense, the research conjectures about the changes that occurred in the world of work in the era of capital, discussing the meaning of work and how it impacts the various social aspects of the individual. The expectation of carrying out professional education within the omnilateral perspective constitutes a possibility for man's emancipation through training. Given this assumption, the research aimed to understand in which aspects Professional Education enables or not an omnilateral human formation, and more specifically, to analyze the transformations that have taken place in the world of work in the materiality of the capitalist system and to discuss the conception of work, weaving theories about training for work. To meet the stated objective, the research is characterized as a theoretical analysis, structured from the dialectical method, in the historical materialist perspective, bringing to light theories, authors and criticisms about omnilateral formation. The foundation that theoretically guides the research is anchored in the concepts of work and society proposed by Marx (1992, 2013) and Marxian theorists, studies on omnilaterality, education and work presented mainly by Saviani (2007), Mészáros (2008) and Antunes (2004, 2007, 2019, 2020). Seeking to draw a consistent perspective on the possibility of omnilateral training for Brazilian professional education, the research on human training in the training process of professional education at Pronatec was initially taken as a basis. However, two major motivators led us to adopt a new research methodology, the COVID-19 pandemic and the end of the government program, which took place in 2019. In this sense, the research is structured as a theoretical analysis of the guiding principles of the Pronatec program and the program instituted as a substitute for this one, Novos Caminhos. With this principle, the research presents theories that generate possible reflections about the integral human formation in its broad physical, intellectual and technological faculties, defining the perspectives that involve the concept of omnilaterality and unveils the (im)possibilities of this formation model in the way of capitalist production.